Native Valve Endocarditis due to Enterococcus hirae Presenting as a Neurological Deficit - Renato Anghinah; Rafael Gustavo Sato Watanabe; Mateus Mistieri Simabukuro; Carla Guariglia; Lécio Figueira Pinto; Daniella Costa de Menezes e Gonçalves (Case Reports in Neurological Medicine)
Enterococcus hirae is a rare isolate in clinical specimens. We describe a case of native aortic valve endocarditis in a 56-year-old man. This is the third reported case of endocarditis due to this organism, the first without recurrence of endocarditis and the first presenting as a neurological deficit.